2018
DOI: 10.1080/10872981.2018.1432231
|View full text |Cite
|
Sign up to set email alerts
|

Is it a match? a novel method of evaluating medical school success

Abstract: Background: Medical education program evaluation allows for curricular improvements to both Undergraduate (UME) and Graduate Medical Education (GME). UME programs are left with little more than match rates and self-report to evaluate success of graduates in The Match.Objective: This manuscript shares a novel method of program evaluation through a systematic assessment of Match outcomes.Design: Surveys were developed and distributed to Program Training Directors (PTDs) at our institution to classify residency p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Although different comprehensive evaluation models [1–3] are available for curriculum evaluation, medical schools are constantly looking for innovative ways to evaluate their curricula, especially if the evaluation method responds efficiently in making recommendations and changes. For instance, Chang et al [4] utilized medical student graduates’ ability to match in highly regarded residency programs as a measure of undergraduate medical education program quality. They also reported that key factors in students finding “elite” residency programs were “clerkship grades and Step 1 scores” [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although different comprehensive evaluation models [1–3] are available for curriculum evaluation, medical schools are constantly looking for innovative ways to evaluate their curricula, especially if the evaluation method responds efficiently in making recommendations and changes. For instance, Chang et al [4] utilized medical student graduates’ ability to match in highly regarded residency programs as a measure of undergraduate medical education program quality. They also reported that key factors in students finding “elite” residency programs were “clerkship grades and Step 1 scores” [4].…”
Section: Introductionmentioning
confidence: 99%
“…While physicians are by nature quantitative [13], in one 2001 survey-driven study of internal medicine residency program directors, the determination of quality of the match was a subjective assessment of 'matched much better/somewhat better/ same/somewhat worse/much worse than previous [years]' [14]. Our study differs from another prior study [8] in the use of hypothetical match lists to determine the impact of variables on the interpretation of match success. In addition, our survey methodology included assessments made by student affairs experts from multiple institutions as opposed to a single center.…”
Section: Discussionmentioning
confidence: 99%
“…The 18 included specialties in the NRMP match plus specialties from the other matches (urology, ophthalmology) were grouped based upon their applicants/available positions ratios, with three possible outcomes: matching into a highly competitive specialty, matching into a moderately competitive specialty, and matching into a less competitive specialty (see Table 1) [9][10][11]. Reputation of the institution, adapted from methods described in other studies [8,12], was binary: whether or not the matched program was among the top 10 in terms of NIH funding. Each factitious mini-match list fulfilled one condition: Matching Status (four possible outcomes) x Competitiveness (three possible outcomes) × Reputation (two possible outcomes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, students have no incentive or reward to falsify this data. The Electronic Residency Application System (ERAS) which holds the information on first, second or third choice match, does not officially release this information, thus all medical schools in the United States must rely on self-reported data [27]. Additionally, in the present study, data on the specific specialty and residency program that students matched into was also self-reported.…”
Section: Discussionmentioning
confidence: 99%